Universal Design: A Step toward Successful Aging - Kelly Carr; Patricia L. Weir; Dory Azar; Nadia R. Azar (Journal of Aging Research)
The concept of aging successfully has become increasingly important as demographics shift towards an aging population. Successful aging has been defined to include (1) a low probability of disease and disease-related disability; (2) a high level of physical and cognitive functioning; and (3) an active engagement in life. The built environment can create opportunities or constraints for seniors to participate in social and productive activities. Universally designed spaces are more easily accessed and used by a spectrum of people without specialized adaptations. Thus, a universally designed environment creates opportunities for older adults to participate in these activities without the stigmatization associated with adapted or accessible designs. Providing older adults with specific universal design options (e.g., lever handle faucets) has the potential to increase the ease of completing activities of daily living, which promotes a continual engagement in life. Literature regarding universal design is promising; however, its theory requires further attention from professionals designing the built environment, evidence of the significance of its application from academics, and the embracement of its core principles from society. Overall, universal design has the potential to provide a stepping stone toward successful aging.